Unifying and benchmarking state-of-the-art quantum error mitigation techniques - Bultrini, Daniel; Gordon, Max Hunter; Czarnik, Piotr; Arrasmith, Andrew; Cerezo, M.; Coles, Patrick J.; Cincio, Lukasz (Quantum, 2023)
Daniel Bultrini, Max Hunter Gordon, Piotr Czarnik, Andrew Arrasmith, M. Cerezo, Patrick J. Coles, and Lukasz Cincio, - Quantum 7, 1034 (2023). - Error mitigation is an essential component of achieving a practical quantum advantage in the near term, and a number of different approaches have been proposed. In this work, we recognize th…
Gesehen am 11.10.2023